2007
DOI: 10.1097/mlg.0b013e31812e960d
|View full text |Cite
|
Sign up to set email alerts
|

Return of Vocal Cord Movement: An Independent Predictor of Response to Nonsurgical Management of Laryngeal Cancers

Abstract: The immobile vocal cord is associated with a worse prognosis and is therefore factored into the American Joint Commission on Cancer staging for laryngeal tumors. We show that vocal cord immobility is an independent prognostic factor of recurrence even after treatment and can predict treatment failure in T2 and T3 lesions of the larynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Nine patients were treated with radiotherapy alone, and five patients were treated with chemoradiotherapy. Five of 14 patients did not have return of vocal cord function, and all had locoregional recurrence, whereas none of those who had return of function had a recurrence 7…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nine patients were treated with radiotherapy alone, and five patients were treated with chemoradiotherapy. Five of 14 patients did not have return of vocal cord function, and all had locoregional recurrence, whereas none of those who had return of function had a recurrence 7…”
Section: Discussionmentioning
confidence: 91%
“…Fixed vocal cord lesions are indicative of deep muscle or cartilage infiltration, and thus, under the American Joint Committee on Cancer (AJCC) classification, they are given at least a T3 designation 4. Return of vocal cord function after nonsurgical therapy, however, may predict a better outcome 5–7…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, radiotherapy is drastically less effective for lesions associated with decreased vocal fold mobility; a return to normal mobility after therapy is an independent prognostic factor regardless of the number of local recurrences. 11 Other factors associated with a poorer prognosis is disease extension to the subglottis and the piriform recess. 2 A published series has shown that the presence of an intermediate signal on the thyroid cartilage of patients with T2 tumors in magnetic resonance imaging highly suggested invasion of the thyroid cartilage and a worse prognosis.…”
mentioning
confidence: 99%
“…They concluded that the persistence of vocal cord immobility was a poor prognostic indicator and a predictor of treatment failure. 7 In contrast to the above studies, we included only patients with T3/T4 SCC of the larynx with vocal cord fixation treated with cisplatin-based chemoradiotherapy. Our findings support and confirm the knowledge that the return of vocal cord function after chemoradiotherapy is a good prognostic indicator.…”
Section: Introduction Introduction Results Resultsmentioning
confidence: 99%
“…4 Return of vocal cord function after non-surgical therapy, however, may predict a better outcome. [5][6][7] At our institution concurrent chemoradiotherapy has been used as a definitive treatment option for SCC of the larynx. Our purpose was to cull our experience with T3/T4 laryngeal SCC and pre-treatment vocal cord fixation to evaluate non-surgical management outcomes and further to assess the implications of persistent post-treatment vocal cord immobility.…”
mentioning
confidence: 99%